Rate of Vaccination of Children at Diyala Province & the Effect of Parental Education on Vaccination Status, Hospital Based Study - Mahmood , Najdat Shukur (Diyala Journal of Medicine, 2019)
Background: Iraq is one of the countries which applicated routine vaccination schedule many years ago, however, still many infectious diseases attack children , e.g. whooping cough & tuberculosis, which was supposed to be absent or decreased dramatically by such vaccination program like what was happened at many developed countries since decades. Many causes had been implicated; one of these reasons may be the response of the population to that program. In Iraq, all the vaccines were given freely & the visits are voluntary, furthermore, many T.V. & Radio programs & newspapers urge the people towards vaccination, nevertheless, many children had not been vaccinated as we see in our clinical practice, but we don’t know to which degree this problem is present. So this study was came as a trial to expose some of secrets of this problem by finding the rate of vaccination, although it was a hospital based data, but it may give an idea about the vaccination status in the province, in addition, the effect of parental education on population compliance to the schedule will be searched. Patient & method: The study was done at Al- Batool teaching hospital for maternity & children at Baquba city from 1st of September 2011 – 1st of September 2012, random sample was collected from both in- & out-patients, it involved children of one year old or below, history of immunization of those children according to the Iraqi schedule of vaccination was taken from parents, supported by vaccination card if it was available, in addition to the academic achievement of parents, then calculation & statistical analysis. Results: The immunization status of 259 child had been reviewed with the parents. Those were fully vaccinated children (in 180 child (70%)), partially vaccinated children (in 63 child (24%)) , & non- vaccinated children (in 16 (6 %)). Both mother’s & father’s education had positive significant effect on the compliance of the parents to vaccinate their children (p value was 0.000 & 0.001, respectively). Conclusion: Rate of vaccination at this study was higher than that found in Iraq at 2010, but not reached to the level of well economic countries. We are need to encourage vaccination, at the same time explaining their side effects & ways of management in front of vaccinations benefits to break up any refusal idea.